Commentary on a "unified approach to behaviours that challenge": my freedom – the perspective of people with learning disabilities. Issue 3 (27th November 2020) - Chapman, Steve; Lillis, Michael; Lamb, Sammy; Clifton, Matt; Clay, Charlotte
Abstract : Purpose: As self-advocate leaders, the authors aim to present the perspective of people with learning disabilities on "Behaviour that Challenges: A Unified Approach". Building on firsthand accounts which reveal compassion and cruelty in the health-care system, the authors propose ways of working, which confirm and add to the thinking in "A Unified Approach", especially "Capable Environments". Design/methodology/approach: To ensure integrity, the authors engaged contributors with lived experience of admission to secure care after acting in ways that put themselves or others at risk. The authors included the perspective of people whose severe learning disabilities limit them to few or no words as best they could by interviewing their parents. The authors were supported and advised in the writing of this commentary while retaining full control throughout. Findings: While recognising compassionate care, the authors suggest the provider's power over a person's life is a central reason for the care system's vulnerability to the cruelty evident in firsthand accounts. The authors propose practical ways to offset this power. Firsthand accounts suggest the key features of capable environments are communication, valuing families and developing a valued, caring, well-trained workforce. Lived experience in workforce training and peer-support to individuals offer great potential to transform outcomes. Originality/value: The perspectives of diverse contributors with learning disabilities bring lived experience insight to the challenges of "behaviour that challenges". The authors aim to add value by blending lived experience viewpoints with the emotion of firsthand accounts of care. The insights of lived experience – too often a marginal consideration in health-care design – are presented here as central to care that fully achieves what people want and need.